2022
DOI: 10.1016/j.jpainsymman.2021.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Core Domains to Assess the “Quality of Death”: A Scoping Review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 245 publications
(510 reference statements)
0
2
0
Order By: Relevance
“…First, we undertook an extensive scoping review that identified the core domains of end-of-life care that matter most to patients, and caregivers (Bhadelia, A et al, 2021 forthcoming). 12 Second, we developed a discrete choice experiment (DCE) survey to produce preference weights associated with each of the key indicators of EOL care identified in the scoping review (Gonzalez-Sepulveda, JM 2021 forthcoming). 13 Finally, as reported in this article, we developed, and fielded a survey for country-experts around the world who were qualified to assess the quality of EOL care within their country.…”
Section: Methodsmentioning
confidence: 99%
“…First, we undertook an extensive scoping review that identified the core domains of end-of-life care that matter most to patients, and caregivers (Bhadelia, A et al, 2021 forthcoming). 12 Second, we developed a discrete choice experiment (DCE) survey to produce preference weights associated with each of the key indicators of EOL care identified in the scoping review (Gonzalez-Sepulveda, JM 2021 forthcoming). 13 Finally, as reported in this article, we developed, and fielded a survey for country-experts around the world who were qualified to assess the quality of EOL care within their country.…”
Section: Methodsmentioning
confidence: 99%
“…Building on a recently published scoping review that identifies core domains and sub-domains of EOL care, 10 we developed a candidate list of EOL care indicators. These indicators were refined with the help of palliative-care experts.…”
Section: Methodsmentioning
confidence: 99%
“… 15 Through family member evaluation of the QODD frequency component, we previously identified 4 distinct QODD classes (high, moderate, poor to uncertain, and worst) characterized by patients’ physical symptom control, emotional preparedness for death, and amount of life-sustaining treatments (LSTs) received, 22 reflecting the core domains for quality of death. 23 …”
Section: Introductionmentioning
confidence: 99%